Evidence in Education (LEARNing Landscapes, 2010)
How much can we reasonably expect from research in education? There are many reasons to think the effects could be both powerful and positive. The call to make more use of research evidence does not in any way conflict with professional autonomy; if anything, it reinforces it.There are many areas of education where we do not have enough evidence to be confident about what to do. However, there are areas where we do have enough knowledge and yet are not applying it broadly. The take-up of evidence greatly depends on professionals’ belief that their work should be guided by reliable knowledge, yet that belief is itself largely created by social practices and communication patterns. Many of the necessary elements to do so are simply not there today in most schools or school systems. Many of these features could be reinforced with relatively little effort with good results for students.
Keywords: research; education; professional autonomy; evidence; reliable knowledge; social practice; communication pattern; school